THE RELATION BETWEEN INTERNET, DEPRESSION, SELF-ESTEEM AND SOCIAL ATTACHMENT ON COGNITIVE FUNCTION OF HEALTH CARE INDIVIDUALS - Ramasubramanian, Vikhram; Venkataraman, Rajesh; Pandian, Raja Soundara; Teli, Gopal; Shrestha, Niraj (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: To assess the internet use in health care individuals and its impact on depression, self-esteem and social attachment on cognitive function of health care individuals. Methods: This was a cross-sectional survey which included one hundred and ten healthcare individuals (Physician, Pharmacist, Psychologist, Social worker and Nurses) in this study conducted in Radianz healthcare and research private limited. Young's internet addiction test and depression score, self-esteem (Rosenberg's) score and MoCA were used to measure internet addiction and psychological variables. EPI 2012 was used for statistical analysis. Results: Out of 110 individuals, the majority of individuals, depressed individual were more addicted to the internet and found to be significant by using depression score. Relationship between baseline values and follow up values in internet addiction was significant (P=0.07636). After follow up the internet addiction found to be reduced as it was greatly affected in initial survey. Conclusion: This study concluded that there is relationship between the internet addiction and depression, cognitive function and self-steam. The depressed individuals were more addicted to the internet followed by abnormal cognitive function and low self-esteem individuals. Internet addiction may be a relevant clinical construct and early diagnostic tools that needs extensive research even in developing nations to explore the relationship. Depression is greatly associated with the internet addiction so if can we reduce the depression then can be reduced internet addiction.